The role of α-tubulin tyrosination in controlling the structure and function of hippocampal neurons - Hosseini, Shirin; van Ham, Marco; Erck, Christian; Korte, Martin; Michaelsen-Preusse, Kristin (Frontiers in Molecular Neuroscience, 2022)
Microtubules (MTs) are central components of the neuronal cytoskeleton and play a critical role in CNS integrity, function, and plasticity. Neuronal MTs are diverse due to extensive post-translational modifications (PTMs), particularly detyrosination/tyrosination, in which the C-terminal tyrosine of α-tubulin is cyclically removed by a carboxypeptidase and reattached by a tubulin-tyrosine ligase (TTL). The detyrosination/tyrosination cycle of MTs has been shown to be an important regulator of MT dynamics in neurons. TTL-null mice exhibit impaired neuronal organization and die immediately after birth, indicating TTL function is vital to the CNS. However, the detailed cellular role of TTL during development and in the adult brain remains elusive. Here, we demonstrate that conditional deletion of TTL in the neocortex and hippocampus during network development results in a pathophysiological phenotype defined by incomplete development of the corpus callosum and anterior commissures due to axonal growth arrest. TTL loss was also associated with a deficit in spatial learning, impaired synaptic plasticity, and reduced number of spines in hippocampal neurons, suggesting that TTL also plays a critical role in hippocampal network development. TTL deletion after postnatal development, specifically in the hippocampus and in cultured hippocampal neurons, led to a loss of spines and impaired spine structural plasticity. This indicates a novel and important function of TTL for synaptic plasticity in the adult brain. In conclusion, this study reveals the importance of α-tubulin tyrosination, which defines the dynamics of MTs, in controlling proper network formation and suggests TTL-mediated tyrosination as a new key determinant of synaptic plasticity in the adult brain.